Integrating Intercultural Digital Literacy in EFL Classrooms: Strategies for Enhancing Students’ Intercultural Competence in the Digital Era - Marwa Marwa; Muliardi Muliardi; Raudhah Awal; Hengki Irawan (STAI Hubbulwathan Duri, 2025)
In an increasingly globalized and digitally connected world, developing intercultural digital literacy—the ability to critically engage with diverse cultures through digital platforms—is vital for English as a Foreign Language (EFL) learners. This study investigates how intercultural digital literacy can be effectively integrated into EFL instruction to enhance students' intercultural competence and global communication skills. A qualitative phenomenological approach was employed, focusing on an English Study Program at a university in Riau, Indonesia in 2024. Data were collected through semi-structured interviews with two lecturers and one third-semester EFL class, supported by classroom observations and document analysis. Thematic analysis was used to identify recurring patterns and insights. Findings indicate that integrating digital tools such as task-based learning activities, online discussions, and social media platforms significantly supports the development of intercultural digital literacy. These strategies foster critical thinking, cultural awareness, and digital communication skills among students. The results underscore the importance of embedding intercultural elements within digital learning environments to prepare students for cross-cultural interaction. Teachers play a pivotal role in curating meaningful digital experiences that promote intercultural competence. This study highlights the value of intercultural digital literacy in EFL education and its potential to enhance global readiness among students. Future research should further explore innovative digital approaches and address existing challenges in implementation.